DAMPAK KEUANGAN BANK SYARIAH DI MASA PANDEMI COVID 19 - Dewi Jayanti (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2021)
Novel Corona Virus Covid-19 pandemic has globally and significantly created a huge impact in the development of economic world and has become challenges to small and medium enterprise, and industrial service of finance and banking. This situation, moreover, may worsen the finance system including bank interest in a conventional bank. This study aims to examine the management of operational strategy applied by an Islamic banking to carry out its functions as an institution of banking intermediation such as raising funds and distributing them in the Covid-19 pandemic situation. This study also aims to provide understanding of how the Islamic finance carries out its intermediation functions in the middle of Covid-19 pandemic. The methodology used in this study is qualitative by using naturalistic approach because of its natural situation in conducting the study. The data was analyzed using analysis descriptive. The results showed that the Covid-19 pandemic has impacts toward functions of banking intermediation in terms of funding and third-party funds (TPF). In addition, the Islamic bank tends to increase from January to March 2020. Furthermore, due to the Covid-19 pandemic, the management of banking operational strategies and the third-party funds (TPF) of the Islamic bank encounters a fluctuating phase